Progesterone, cervical cerclage or cervical pessary to prevent preterm birth: a decision-making analysis of international guidelines - Putora Katharina; Hornung René; Kinkel Janis; Fischer Tina; Putora Paul Martin (BMC, 2022)
Abstract Objective The aim of this study was to investigate guidelines on preterm birth, analyze decision-criteria, and to identify consensus and discrepancies among these guidelines. Design Objective consensus analysis of guidelines. Sample Ten international guidelines on preterm birth. Methods Relevant decision criteria were singleton vs. twin pregnancy, history, cervical length, and cervical surgery / trauma or Mullerian anomaly. Eight treatment recommendations were extracted. For each decision-making criteria the most commonly recommended treatment was identified, and the level of consensus was evaluated. Main outcome measures Consensus and Discrepancies among recommendations. Results In a case of singleton pregnancies with no history of preterm birth and shortened cervix, most guidelines recommend progesterone. In singleton pregnancies with a positive history and shortened cervix, all guidelines recommend a cerclage as an option, alternative or conjunct to progesterone. The majority of the guidelines advise against treatment in twin pregnancies. Conclusions A shortened cervix and a history of preterm birth are relevant in singleton pregnancies. In twins, most guidelines recommend no active treatment. Tweetable abstract Among international guidelines a shortened cervix and a history of preterm birth are relevant in singleton pregnancies. With no history of preterm birth and with a shortened cervix most guidelines recommend progesterone treatment.